Ar livre e carne em abundância um estudo histórico-cultural do gaucho e sua alimentação no século XIX - Nobre, Chimene Kuhn (2011)
The object of this research were the remains of Bos taurus catalog 060 rescued in the archaeological site RS-Q-17 - Estância Velha do Jarau, that this site has been researched by the Laboratório de Estudo e Pesquisa em Arqueologia (LEPA/UFSM), since 1997, with coordination archaeologist Dr. Saul Eduardo Seiguer Milder. The archaeological site is located on the southwestern border of Rio Grande do Sul, an area marked by constant conflicts that occurred during the consolidation period and definition of the state territory, where the habits, customs and food had a direct influence of the uruguayan and argentine culture. Of material culture found, archaeofauna represents a significant portion in terms of quantity. Thus, the main purpose of this research was to identify, analyze and interpret this archaeofauna quantitatively and qualitatively, so that made it possible to demonstrate through the bony elements identified that the diet of the preterit occupants of this archaeological site located on the southwestern border of Rio Grande do Sul was very diverse. The menu included the consumption of beef in the form of baked, stewed, fried and baked. A small portion of the collection archaeofaunistical shown to have been consumed in the form of barbecue: ribs. A large majority of elements were parts of long bones and bones of the feet and consumed in stews or boiled for supporting a variety in the way of preparation. Although beef is the preferred type, the barbecue is not the same level of importance and control daily food as the historical gaucho tradition affirms.